Transformation of the private healthcare sector in the Republic of Kazakhstan following healthcare reforms - Alibek, Smagulov; Kuralbay, Kurakbayev; Abylai, Baimakhanov; Olzhas, Zhandossov; Nazerke, Abilkaiyr; Maiya, Zhakupova; Magripa, Bapayeva; Gulnara, Kapanova; Galiya, Alikeyeva; Dinara, Makhanbetkulova (Frontiers in Public Health, 2025)
BackgroundIn Kazakhstan, transformation of the private healthcare sector as the country transitioned from lower-middle-income to upper-middle-income status has rarely been a subject of academic debate. This study aimed to analyze of health sector indicators disaggregated by type of ownership over the period of 10 years (from 2011 to 2020).MethodsThis was a retrospective cross-sectional study, which was based on official healthcare statistics presented by the Ministry of Health. Relative change (RC) was computed to identify trends in changes over time and was expressed as a proportion with 95% confidence intervals.ResultsIn contrast with the government-owned health facilities, the overall number of private facilities increased over time, although this growth was less obvious in per capita terms. The number and density of private PHC facilities grew more substantially than those of outpatient facilities. PHC practitioners employed by the government-owned facilities admit more patients than practitioners of the private PHC facilities do. There is an uneven presence of the private health sector in different medical specialties with maternity, ophthalmology, dentistry, narcology, multidisciplinary, as well as palliative and nursing care being the most common.ConclusionSuch data are needed by decision-makers to tailor public health strategies focused on the stewardship of the private health sector, which would help improve the availability and affordability of medical services.